Pengembangan Poster sebagai Media Promosi Pencegahan COVID-19 - Henni Febriawati; Delvita Efrianti; Riska Yanuarti; Oktarianita Oktarianita; Wulan Angraini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to develop health promotion media for COVID-19 prevention posters at the Muhammadiyah University of Bengkulu. The research method used in this research is Research & Development using the Bogh & Gall research model. The results of the design validation research for material experts get a feasibility percentage of 75% in the very feasible eligibility category, media experts get a feasibility percentage of 77% in the very feasible feasibility category, and linguists get a feasibility percentage of 75% in the very feasible type. The results of the small group product trials obtained a feasibility percentage of 87.81% with the very feasible feasibility category. This research is limited to developing COVID-19 prevention poster media and is only carried out until the product trial stage. In conclusion, a health promotion media poster for COVID-19 prevention was produced at the Muhammadiyah University of Bengkulu using Canva with product testing on small groups, obtaining an 87% qualification with very qualified eligibility criteria. Keywords: COVID-19, Media Promotion, Poster